Participatory action research in community forestry: A case study of a community forest users' group from a hill village of eastern Nepal - Uprety, Laya Prasad (Occasional Papers in Sociology and Anthropology, 2008)
The PDF of this file is 3,205 kbytes in size and therefore will take a long time to download if you click on the PDF link below. If you would like the file to be sent to you by email, please send a request to info@nepjol.info. Please include the citation below in your request. DOI: 10.3126/opsa.v8i0.1119 Occasional Papers in Sociology and Anthropology Vol.8 2003 p.18-40